Variational framework and Lewy-Stampacchia type estimates for nonlocal operators on Heisenberg group - Goel, Divya; Rădulescu, Vicenţiu D.; Sreenadh, Konijeti (Annales Fennici Mathematici, 2022)
The aim of this article is to derive some Lewy-Stampacchia estimates and the existence of solutions for equations driven by a nonlocal integro-differential operator on the Heisenberg group.